Feeder Pig Nursery Cost Return Projection - Dhuyvetter, Kevin C.; Tokach, Mike D. (My University, 2003)
This publication provides estimated cost and returns for a feeder pig nursery.
MF2151_2003_10
Keywords: MF2151; Livestock; Economics; MF